Csokonai Vitéz Mihály összes művei: Elektronikus kritikai kiadás - Boldog-Bernád, István (Studia Litteraria, 2024)
The text reviews the new scholarly digital edition of The Complete Works of Mihály Csokonai Vitéz. It gives a brief overview of the Hungarian scholarly digital editions and discusses the importance of the TEI-XML markup language. It gives a structural overview of the scholarly digital edition based on genetic principles, argues why it fundamentally changes the reception of Csokonai’s oeuvre, and then illustrates various possible uses through examples.